Venous Thromboembolism in Intensive Care Unit - Tamanna, RJ (University Heart Journal, 2010)
Venous thromoboembolism (VTE) represents a spectrum of disease which includes deep vein thrombosis (DVT) and pulmonary embolism (PE), a common complication in critically ill patients. VTE is difficult to diagnose, expensive to treat and occasionally lethal despite therapy. Therefore preventive measures are paramount. DVT and PE contribute significantly to morbidity and mortality associated with critical illness. But VTE remains an underestimated problem in ICU patients, despite the findings of many randomized controlled trials performed in the fields of DVT prophylaxis during the past few decades This article reviews the risk of VTE in critical care patients, thromboprophylaxis and suggests strategies to reduce the burden of thrombo-embloic disease in critical care unit. Key words: Venous thromoboembolism; Intensive Care Unit. DOI: 10.3329/uhj.v5i2.4562 University Heart Journal Vol.5(2) July 2009 pp.84-88